Kajian Pendidikan Karakter Dalam Cerita Sundara Kanda - Ni Made Wiratini; Ni Komang Sutriyanti; I Gusti Ngurah Sudiana (Cetta: Jurnal Ilmu Pendidikan, 2020)
Hindu teachings contain a lot about character education, morals, ethics and manners. Moral education can be seen in the story of Sundara Kanda, which is a sub of Itihasa in the Ramayana epic that tells the journey of life with various obstacles and tests that must be faced with full fortitude, strength and determination. Every event that occurs in the Sundara Kanda story is a unified narrative unit in resolving the conflict of every event. The setting in this story uses the setting of Mount Mainaka, Alengka Palace, Taman Angsoka, Kiskinda kingdom. The character is Hanuman who becomes a central figure, then there are goddesses Sitā and Ravana. The accompanying figures are Trijata, Wibisana, Anggada, Jembawan, Sugriwa, Laksmana and Rama. Rahwana as the Antagonist, then there are also giants. His mandate is loyalty and determination in carrying out dharma. Character characters contained in the Sundara Kanda story include characterization displayed through the use of the character's name, through the appearance of the character, and characterization through the author's speech. In accordance with the characters contained in Hindu teachings, namely in the book of Bhagawadgita, the characters in the Sundara Kanda story can be grouped into two characters namely daivi sampad and asuri sampad. The values ​​contained in the character of the Sundara Kanda story include religious, honesty, responsibility, tolerance, discipline, and hard work. As a whole, the character's character value is a national character that should be inculcated and developed to the wider community, in order to shape the attitudes and behavior of a person in carrying out the duties and obligations that should be carried out both towards oneself, the family environment, society, nation and state.